VARIABEL-VARIABEL YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE DI BEI - yuliaratih, kadek ayu silvia; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
This study aims to prove empirically factors of Gross Domestic Product (GDP), Rupiah exchange rate, SBI interest rate, inflation, Return On Assets (ROA), Net Profit Margin (NPM), Earning Per Share (EPS) and Price Earning Ratio (PER) to stock return on property and real estate company in Indonesia Stock Exchange in 2012-2016. Research sample is determined by purposive sampling method where the researcher has certain criteria or objective to the sample to be researched as many as 26 emitters which included in property and real estate sector in PT Bursa Efek Indonesia The result of this research is as follows: Gross Domestic Product, Net Profit Margin, Earning Per Share and Price Earning Ratio have positive and significant effect to stock return of property and real estate. The rupiah exchange rate and inflation have a negative and significant effect on stock returns of property and real estate. Furthermore, the SBI interest rate and Return On Assets have a positive and significant effect on stock.